THE ROLES OF ARBUSCULAR MYCORRHIZAE IN SUPPORTING THE MANGROVE GROWTH - Agusrianto Yusuf (Journal of Health, Technology and Science (JHTS), 2021)
The current study aims to determinate the potential of Arbuscular mycorrhizae in supporting the mangrove growth, the role of Arbuscular mycorrhizae on the improvement of mangrove growth in terms of its colonization level with the mangrove roots, the mangrove ability of Arbuscular mycorrhizae in the way of supporting the rehabilitation of mangroves, and giving the recommendation to the local government related to the potential of mycorrhizal fungi in rehabilitating the degraded magrove areas living in the coastal areas of Kwandang, North Gorontalo regency. Moreover, this study used a descriptive qualitative analysis method using ex-post-facto approach. To collect the data, it used a pruposive sampling on rhizosfer and mangrove roots in order to observe the spore density, the diversity and the mycorrhizal colonization. The results of this study show that the ability of Arbuscular mycorrhizae in supporting the mangrove growth is categorized in the high level. It can be seen from the spora density. On average in research location, the number of the spores that were successfully isolated is 42 spores/ 100 grams of soil. Arbuscular mycorrhizae has a role in the way of increasing the mangrove growth. This can be seen from the high percentage of colonization with mangrove roots whereas 57,87%.